Początki dyskursu akademickiego. Jezuickie Assertiones - Lichański, Jakub Z. (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
The purpose of the article is to discuss two problems: first, early academic discourse in shapingthe modern Europe, secondly to describe the Jesuit Assertiones, which can be considered an introductionto modern scientific discourse. The author presents the first evolution of Assertiones, the form and scope.Then fill in what we know today in academic discourse. The investigator also notes that a full descriptionof Assertiones is difficult, because the discussion entry is missing, what was after presentation is also contained in Assertiones. In conclusion the author finds that not only can Assertiones be a specific formof scientific expression in Jesuit schools, form of academic discourse, but that Assertiones significantlyinfluenced later shape academic discourse.